A WHO reference reagent to standardize haemagglutination testing for anti‐A and anti‐B in serum and plasma: international collaborative study to evaluate a candidate preparation. Issue 2 (23rd March 2016) - Thorpe, S. J.; Fox, B.; Sharp, G.; White, J.; Milkins, C.
Abstract : Background and Objectives: The aim of the study was to evaluate a lyophilized serum preparation, 14/300, for its suitability to serve as a World Health Organization (WHO) Reference Reagent to standardize and control haemagglutination titrations for anti‐A and anti‐B in serum and plasma, in an international collaborative study. Materials and Methods: Serum preparation 14/300 and two plasma‐based reserve preparations, 14/304 (high titre anti‐A) and 14/208 (high titre anti‐B), were titrated by 24 laboratories in 13 countries using direct (DRT) and indirect (IAT) haemagglutination techniques. Results: There was eightfold to 64‐fold variation in reported titres per preparation and method across laboratories, that is, titres extended over 4–7 dilutions, although intralaboratory variability was generally good, with over 90% of replicate titres within a twofold range. There was a reduction in interlaboratory variability when titres of the reserve preparations were adjusted relative to those of the candidate Reference Reagent. Conclusion: The establishment of 14/300 as a WHO Reference Reagent for high titre anti‐A and anti‐B in serum, with nominal anti‐A and anti‐B titres of 128 for DRT, and nominal anti‐A and anti‐B titres of 256 for IAT, will facilitate global standardization of haemagglutination titrations for anti‐A and anti‐B in patient samples and blood components.